Reflectarray Antenna for Simultaneous Near-Field Fronthaul and Far-Field Backhaul Links in Next 5G FR2 Femtocells - Alvaro F. Vaquero; Borja Imaz-Lueje; Marcos R. Pino; Manuel Arrebola (IEEE Open Journal of Antennas and Propagation)
This work presents a reflectarray-based base station antenna to integrate both backhaul (BH) and fronthaul (FH). The reflectarray operates at 28 GHz in dual linear polarization, using one polarization for the BH and another for the FH. The BH is a pencil beam of maximum gain pointing in a certain direction, while the FH defines the coverage for a femtocell. The FH is used to generate the coverage within the near field radiated by the base station. The synthesis of the FH is carried out by means of a near-field phase-only synthesis (NF-POS), while the BH is analytic. Both phase-shift distributions are physically implemented using a unit cell based on a double-layer topology of coplanar dipoles. The reflectarray is manufactured and evaluated in a spherical range (far field) and a planar range (near field). The measurements agree with the simulations, showing that a single antenna based on a reflectarray can be used to implement the dual link FH and BH.